2008
DOI: 10.1108/09513570810893263
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary action against members of the founding bodies of the ICAEW

Abstract: Purpose -The purpose of the paper is to present an analysis of the disciplinary action taken against members of the founding bodies of the Institute of Chartered Accountants in England and Wales (ICAEW). This exercise illuminates an aspect of accounting's past which has tended to be overlooked in conventional histories of the profession. Design/methodology/approach -An analysis of the internal records of the ICAEW has been conducted. In addition, the archives of the ICAEW's predecessor bodies, entries in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…George Jay was excluded from the ICAEW in 1891 and in the 1901 census appears as a pawnbroker's clerk resident in a boarding house. Chandler et al (2008) reveal that no fewer than 92 (15.4%) of the founders were expelled from the Institute. While 66 were expelled for non-payment of fees, 15 were bankrupts and 11 committed discreditable acts or misdemeanours.…”
Section: Intragenerational Mobilitymentioning
confidence: 95%
See 3 more Smart Citations
“…George Jay was excluded from the ICAEW in 1891 and in the 1901 census appears as a pawnbroker's clerk resident in a boarding house. Chandler et al (2008) reveal that no fewer than 92 (15.4%) of the founders were expelled from the Institute. While 66 were expelled for non-payment of fees, 15 were bankrupts and 11 committed discreditable acts or misdemeanours.…”
Section: Intragenerational Mobilitymentioning
confidence: 95%
“…Defined by first society joined, 44% of the 600 founders had been members of the Society, an organisation which imposed low membership fees compared to the Institute of Accountants and was considered by contemporaries as having opened its doors rather widely (Walker, 2004b, 32-39, 130-131;Anderson et al, 2007). while owing money to clients (Chandler et al, 2008).…”
Section: Intergenerational Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it also contains negative outliers capable of providing alternative perspectives on the professionalisation of public accountants (e.g. Walker 1996;Edwards 2001;Chandler, Edwards, and Anderson 2005;Lee 2009a). In this study, the alternative perspective is revealed through the backgrounds, lifestyles, and careers of London chartered accountants James Waddell (JW) and William Waddell (WW) who fled to New York in 1883 when impending legislation led to the exposure of their embezzlement of creditor funds.…”
Section: Introductionmentioning
confidence: 97%